The Clock Drawing Task reveals executive dysfunction in the dialysis population – an underrecognized and underestimated problem - Piotr Olejnik; Aleksandra Golenia; Oliwia Maciejewska; Ewa Wojtaszek; Paweł Żebrowski; Jolanta Małyszko (Renal Failure)
Aim of the study The study aimed to assess the prevalence of executive function impairment among patients with chronic kidney disease (CKD) undergoing dialysis, with no subjective cognitive problems and with normal global cognition on the Mini-Mental State Examination (MMSE). We also investigated the relationship between cardiovascular risk factors and cognitive test results.Rationale for the study Patients with CKD, including those undergoing renal replacement therapy, are at a higher risk of developing cognitive impairment (CI) than the general population. Recent research has shown CI to be a growing problem among CKD patients worldwide. Yet, it remains underdiagnosed, even though it may significantly influence the lives of patients.Materials and methods In this cross-sectional, prospective study, 58 dialysis patients with no cognitive decline on the MMSE screening were assessed for executive function impairment using the Executive Clock-Drawing Task (CLOX). Moreover, past medical history, demographic data, and laboratory test results were collected.Results The mean patient age was 59.47 ± 14.98 years, and the mean duration of dialysis was 45.93 ± 48.49 months. The prevalence of executive function impairment amounted to 8.6%. Moreover, remarkably similar pattern of clock drawing was observed, with numbers written outside the clock face in the CLOX1 test.Conclusions Executive dysfunctions in dialysis patients may manifest itself before the onset of global cognitive impairment. There appear to be a deficit in the spatial domain as well. Better education may play a protective role.